Anti-phase synchronization of influenza A/H1N1 and A/H3N2 in Hong Kong and countries in the North Temperate Zone. (January 2018) - Chiu, Alice P.Y.; Lin, Qianying; Tang, Edwin Yiu Nam; He, Daihai
Highlights: The anti-phase patterns between influenza A/H1N1 and A/H3N2 were studied. A/H1N1 and A/H3N2 have shown annual and biannual periodicities in Hong Kong. A/H1N1 and A/H3N2 have shown annual and triannual periodicities in the North Temperate Zone. Anti-phase patterns were found in Hong Kong and the North Temperate Zone. Abstract: Objectives: Influenza affects 10% of the global population annually. Hong Kong is a subtropical city close to the North Temperate Zone (NTZ). Influenza-associated mortality rates in Hong Kong were 27.53, 79.55, 36.94, and 48.72 per one million person-years in 2014, 2015, 2016, and January to July 2017, respectively. The aim of this study was to explore the temporal patterns of influenza A subtypes in both Hong Kong and the NTZ. Methods: Weekly reported cases of influenza A/H1N1 and A/H3N2 from January 2010 to July 2017 were downloaded from the Centre for Health Protection in Hong Kong and FluNet (provided by the World Health Organization). The spatio-temporal patterns of A/H1N1 and A/H3N2 in Hong Kong and the NTZ were explored. Anti-phase synchronization between A/H1N1 and A/H3N2 is indicated by a high for A/H1N1 coinciding with a low for A/H3N2, and vice versa. Results: Anti-phase synchronization was evident in both Hong Kong and the NTZ. It was found that A/H3N2 clearly dominated in the 2011/2012, 2014/2015, and 2016/2017 influenza seasons. Conclusions: These results are novel in identifying anti-phase synchronization in influenza A subtypes in Hong Kong and the NTZ. These findings should inform public health preparedness for future epidemics of A/H3N2, which are typically more severe than those of A/H1N1.